2004
DOI: 10.1021/jp0492523
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Spectral Hole-Burning in Oxygen-Evolving Photosystem II Preparations

Abstract: We present the first report of highly efficient persistent spectral hole-burning in active (oxygen-evolving) Photosystem II (PSII) preparations. Samples are poised in the S1 state of the Kok cycle, with the primary quinone (QA) either neutral or photoreduced to QA - via a low-temperature pre-illumination. Remarkably efficient hole-burning is observed within the chlorophyll Q y (0,0) absorption envelope in the wavelength range of 676−695 nm. The hole-burning action spectrum of a sample poised in the S1(QA -) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
87
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(100 citation statements)
references
References 68 publications
12
87
1
Order By: Relevance
“…These coupling constants are calculated in the dipole-dipole approximation, since the distances between the pigments are >20 Å. Table 3 are ~10 cm -1 , in agreement with the relatively low (on the order of tens of ps) CP43→RC EET rates observed for intact oxygen-evolving PSII core complexes at low temperature 50 .…”
Section: Assignment Of the A And B States To Particular Chlorophylls supporting
confidence: 74%
“…These coupling constants are calculated in the dipole-dipole approximation, since the distances between the pigments are >20 Å. Table 3 are ~10 cm -1 , in agreement with the relatively low (on the order of tens of ps) CP43→RC EET rates observed for intact oxygen-evolving PSII core complexes at low temperature 50 .…”
Section: Assignment Of the A And B States To Particular Chlorophylls supporting
confidence: 74%
“…Although we found very similar intrinsic rate constants for the primary charge separation in intact PSII cores (18) and in isolated D1͞D2-cyt b559 RCs (9), and also supported by studies on CP47͞RCs (11), the identity of the electron transfer mechanism and the rates in intact PSII and RCs has been questioned recently (20)(21)(22)(23) (for recent reviews see refs. 4, 24, and 25).…”
supporting
confidence: 79%
“…The relative weight of the two pathways is determined by specific realization of the disorder in site energies (Novoderezhkin et al 2007). We note here that a recently discovered phenomenon could change our view on primary electron transfer in PS II: a low-lying homogeneously broadened excited state with small oscillator strength was found that is capable of initiating charge separation (Hughes et al 2004;Krausz et al 2005;Hughes et al 2006). At present, this effect is largely unexplained and therefore we will refrain from further speculations.…”
Section: Trapping Of Lightmentioning
confidence: 75%